Campaign individualisation before and after the Bailout: A Comparison between Greece and Portugal - Lisi, Marco (2016)
The elections that took place in Greece and Portugal before and after the intervention of the so-called Troika allow us to examine to what extent the austerity period has affected the nature and style of electoral campaigns, especially in terms of individualisation. Our results show that campaigns in Greece and Portugal were quite different and that Greek candidates supported by the two main parties are more likely to emphasise their role. Yet the short-term impact of the crisis has been negligible, as there have been insignificant shifts in the communicative focus on the personalisation of the agendas and on the means used in the campaign after the intervention of the Troika.